(untitled) - Mark Ptashne (Cambridge, 1992)
The book refines what is known about [lambda], and extends the treatment to consider gene regulation in higher organisms. Three chapters describe the principles of gene regulation in [lambda], and the fourth chapter outlines the experimental bases of the major conclusions. Two new chapters assess how fare gene control in eukaryotes can be considered in terms of the [lambda] model, and what elaborations of the priciples established with [lambda] are necessary to explain more complex programs of gene expression
Keywords: bacteriophage lambda,genetic regulation,viral genetics